THE MODEL OF ENVIRONMENTAL REGULATION BASED ON AN ECOLOGICAL JUSTICE - Tiyas Vika Widyastuti (UNISSULA, 2023)
This research was conducted to find out how strong and efficient the policies made by the government in creating a good living environment in order to achieve an ecological justice. This study uses the Socio Legal Research with the sociology of law approach (sociology jurisprudence). Based on several incidents of environmental damage, one of which was released by AMAN (Alliance of Indigenous Peoples of Indonesia) recorded that there were 40 cases of criminalization and violence against indigenous peoples in 2020. Of the 40 cases, there were 39,069 indigenous people grouped into 18,372 heads of households experience losses both economic, social and moral losses. The total area of the 40 cases reached 31,632.67 hectares. The regulations issued by the government through Act No. 32 of 2009 concerning PPLH its application has not been optimal in environmental management efforts based on ecological justice, this is evidenced by the large amount of environmental destruction especially customary forests carried out by corporations for the benefit of plantations, animal husbandry and others.